Follow-up of the aortic valve replacement surgery in a national reference hospital in Lima, Peru, period 2016-2019 - Figueroa-Alfaro, Carlos (2023)
Objective: To describe the perioperative characteristics of patients undergoing aortic valve replacement; as well as complications, mortality, follow-up and survival. Materials and methods: A retrospective study of patients operated between 2016 and 2019 was carried out. Pre, intra, and postoperative characteristics were determined, as well as clinical and echocardiographic follow-up. Student's t test was used to compare means. Overall survival and cardiovascular event-free survival were analyzed using the Kaplan-Meier method. Results:110 patients were included (59.1% male), the mean age was 65.2 ± 11.3 years, the majority with arterial hypertension (47.3%). The most frequent etiology was degenerative (47.3%). A mechanical prosthesis was implanted in 59.1%. In the postoperative period, a median mechanical ventilation time of 8 hours was observed, with an average stay in the ICU of 5.8 ± 6.7 days. The most frequent complications were atelectasis (21.8%), atrial fibrillation (19.1%), low output syndrome, pneumonia, and acute kidney injury (7.3% each). Hospital mortality was 5.5% (cardiogenic shock as the frequent cause). During follow-up at one year, there was an improvement from NYHA II-III functional class (pre-surgical) to NYHA I-II (p <0.001), prosthesis dysfunction was found in 13.3% (the majority due to paravalvular leak). Overall survival at 1, 3, and 5 years was 88,2 ± 3,1, 83.4 ± 3.6% y 74.3 ± 5.0%, respectively. Conclusions: Aortic valve replacement surgery in our setting implies an improvement in quality of life with good functional results, complication rate, and morbidity and mortality comparable with the world literature.